Pyrite roasting, an alternative to sulphur burning - Synopsis (The Southern African Institute of Mining and Metallurgy, 2009)
The roasting of sulphide ores and concentrates is often the first step in the production of metals or chemicals. In many processes, the production of sulphuric acid is viewed as a by-product, whereas in some plants production is an important economic factor. Regardless of the purpose, a pyrite roasting plant consists of mainly three plant sections: roasting, gas cleaning and sulphuric acid. With the addition of air, the pyrite concentrates are transformed into solid oxides and gaseous sulphur dioxide at temperatures of 600?1000°C. After cleaning and cooling, the sulphur dioxide in the roasting gas is further processed to sulphuric acid. Two types of reactors are used depending on the application: stationary or circulating fluid bed. For over 60 years, Outotec has progressively been developing the principle of fluidized bed technology in several different reactor types for a multitude of process applications. The versatility of the fluidized bed reactor system has manifested itself in the treatment of minerals, including solid fuels, and for metallurgical processes both in the ferrous and non-ferrous fields. Process applications have included roasting, calcining, combustion and charring of coals, as well as off-gas treatment. This paper provides a summary of the pyrite roasting technology currently used along with a simple cost comparison of pyrite roasting and sulphur burning processes.